Peranan Organisasi Kemahasiswaan Dewan Perwakilan Mahasiswa (DPM) Universitas Udayana Dalam Pengembangan Berpikir Kritis Mahasiswa - Jovianto, Fakhri; Arjawa, I Gusti Putu Bagus Suka; Mahadewi, Ni Made Anggita Sastri (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2023)
This study focuses on members of the Student Representative Council. The aim of the research is to describe and analyze the development of critical thinking for members of the Udayana University Student Representative Council. Critical thinking can be developed in various ways, one of which is by joining a student organization engaged in the legislative field at Udayana University, namely the Student Representative Council. Students participating in student organizations can consider various things, especially for students who have various activities and obligations that make students have to think carefully about their decision to join. This study uses a qualitative approach with explanatory descriptive type. Amitai Etzioni's Theory of Communitarianism is used as a scalpel to analyze student choices for the development of critical thinking and challenges of critical thinking in the Student Representative Council student organization. Communitarianism emphasizes the importance of social solidarity and cooperation in achieving common prosperity. Students who participate in the Student Representative Council determine their choice to develop critical thinking by considering it as a communitarian view, that is, this view rejects the view of individualism which prioritizes individual interests above the interests of the community. It was concluded that the development of critical thinking for members of the Student Representative Council has the benefit of developing their legislative skills through various work programs according to the main tasks and functions of advocacy, oversight, legislation and budget aspirations to achieve organizational goals, namely student welfare. It is recommended to carry out the main tasks and functions carried out by each DPM member by prioritizing social solidarity and cooperation with fellow organizations. Keywords: Critical Thinking, Communitarianism, Student Representative Council, Student Welfare